Evaluating sound horeg through maqāṣid-based legal reasoning: A maqāṣid assessment of a contemporary cultural practice in Indonesia - Muhammad Najih Vargholy; Zulfiqar Bhisma Putra Rozi (Ex Aequo Et Bono Journal Of Law, 2026)
Background: Sound horeg is a grassroots sound culture from East Java, Indonesia, characterized by extremely loud sound systems. This phenomenon has sparked debate over whether its economic benefits can justify its associated public health harms under Islamic legal principles. This study examines whether sound horeg constitutes legitimate maslahah or should instead be regarded as mafsadah within Ibn ʿĀshūr's maqāṣid al-sharīʿah framework. Methods: This study employs a doctrinal legal research method. The research combines maqāṣid-based legal reasoning with information from economic and public health sources. Legal materials were collected through library research and analyzed using doctrinal analysis and thematic synthesis. Findings: This study indicates that sound horeg provides limited economic benefits that are often temporary and inconsistent. In contrast, substantial evidence indicates that sound horeg poses significant health risks, including hearing damage, cognitive impairment, and psychosocial stress. These documented harms provide the basis for assessing sound horeg within the maqāṣid al-sharīʿah framework. From this perspective, they threaten the preservation of life (ḥifẓ al-nafs), intellect (ḥifẓ al-ʿaql), and public welfare. Conclusion: This study concludes that sound horeg cannot be regarded as legitimate maslahah under maqāṣid al-sharīʿah because its documented harms outweigh its limited economic benefits. Novelty/Originality of this Article: This article integrates cultural practice, public health, the creative economy, and Islamic legal theory into a maqāṣid-based legal assessment. It demonstrates the application of maqāṣid-based legal reasoning in evaluating contemporary cultural practices.